Concepções de criação musical na prática docente no contexto da colonialidade e na perspectiva da humanização - Galon, Mariana da Silva (2021)
The present thesis aims for pointing out the conception that music teachers specializing in Music Education at Claretiano University hold regarding the role of music creation in early music initiation studies and how these conceptions interfere in their offering of music creation activities. It then considers possibilities of transformation of these views through awareness and reflections upon the subject as well as practical experience in musical creation. We depart for the hypothesis that the colonial legacy has marginalized the knowledge, practice, and other forms of teaching music, thus rendering a sole view as legitimate. The conservatorial, or traditional model, which is a product of colonial influence on knowledge, is present on various levels in education in brasil. This model of education, disregards musical creation actives in initiation studies as one that presents valid results, and holds that not only a minority of people are capable of music creation but that the creational process is only possible after acquiring sufficient theoretical knowledge and technical skills. A big part of music educators adopts these views which effectively hinders the possibility of offering musical creation activities in their teaching process. Based on theoretical studies of authors like Oscar Odena and Pamela Burnard, we believe that it is possible for novice students to effectively engage in music creation actives. Furthermore, we bring forth a new concept of music creation departing from authors like Enrique Dussel, Paulo Freire, Boaventura de Souza Santos, and Anibal Quijano, which leads us to believe in the possibility of the dissolution of traditional model through an awareness process leading to a real change of perspective on music creation and thus, providing space for legitimizing new theories already established abroad. A qualitative study was conducted aiming to analyze and intervene in a reality in order to promote changes based on scientific concepts. Data collection was carried during the year 2018 through a structured questionnaire, narrative construction, photovoice, practice of music creation, discussion forums, and field notes. Data triangulation made visible the following categories: 1) Research collaborator´s Conceptions of musical creation; 2) Music education and teacher training: influences on musical creativity; 3) Difficulties and facilities in offering activates of music creation; 4) Creative process; 5) Change of views regarding music creation. From the results obtained out of this research, we defend the thesis that the coloniality of knowledge leads to the absence of music creation in initiation studies. However, promoting awareness regarding the importance of the subject in music education can lead to a change of perspective and thus impacting creative practices in class.